Detection of Malicious software and control using Artificial Intelligence: Syed Khurram Hassan, Muhammad Asif Ibrahim - Syed Khurram Hassan; Muhammad Asif Ibrahim (International Journal for Electronic Crime Investigation, 2023)
Due to growing pervasiveness of malware in the contemporary digital environment, it is imperative to establish efficient identification and management systems to protect computer systems and networks. Conventional approaches to malware detection frequently encounter difficulties in keeping pace with the swiftly progressing characteristics of malevolent software. However, the emergence of artificial intelligence (AI) has unlocked fresh prospects for augmenting malware detection and control. This article investigates the implementation of AI methodologies in malware detection and mitigation, elucidating the benefits and obstacles connected with this strategy.